THE IMPORTANCE OF PUBLICATION OF MEDIA CONTENT BY THE KUDUS DISTRICT IN PROMOTING TOURIST DESTINATIONS IN KUDUS DISTRICT - Muhammad Aniq Mirza Hilmi (RADJA PUBLIKA, 2025)
This research aims to determine the importance of media content publication by the Kudus Culture and Tourism Department in promoting tourist destinations in Kudus district. This research uses a qualitative research method with a descriptive approach that uses two data sources, namely primary and secondary. Primary data is data obtained from observations and interviews, while secondary data is data obtained through literature studies in the form of journal books, articles and scientific journals related to the importance of media content publications in promoting tourist destinations. In helping to increase public awareness about tourist destinations in Kudus. Through various media platforms, Disbudpar can introduce tourist attractions that may not be widely known to the public. Increased visibility has the potential to attract more tourists, both domestic and international. Disseminating accurate information, Disbudpar can provide the latest information about tourist destinations, history, traditions, arts and culture events, nature, creative economy and available facilities. Media content that is packaged creatively and informatively can improve integrated marketing strategies, assist in crisis management, and encourage innovation in tourism promotion and attract potential tourists to visit Kudus. Apart from that, consistent publications also play a role in forming a positive image of Kudus as an attractive tourist destination. By utilizing YouTube, Instagram, Facebook and so on, Kudus Disbudpar can reach a wider and more diverse target audience. This has the potential to increase the number of tourist visits which will ultimately have a positive impact on the regional economy.